TINJAUAN LITERATUR: HUBUNGAN ANTARA SELF-REGULATED LEARNING DAN EFIKASI DIRI DENGAN PRESTASI AKADEMIK MAHASISWA - Perdana, Yulius Wahyu; Handoko, Martinus Tukir; Eriany, Praharesti (Program Studi Pendidikan Vokasi Seni Kuliner, 2024)
Students are individuals who receive education at the higher education level. Students are able to have the freedom to choose and to determine an attitude that can be accounted for. The aim of this study is to explore the development of research on the relationship between Self-Regulated Learning and self-efficacy with student academic achievement. The method used was Preferred Reporting Items for Systematic Reviews (PRISMA). Literature search by utilizing search engines, namely google scholar, academia.edu, and other platforms using the keywords Self-Regulated Learning, self-efficacy, and academic achievement. The results of the article review of 18 articles were found that Self-Regulated Learning and self-efficacy have a positive relationship with student academic achievement. Self-efficacy in students can also support the implementation of the Self-Regulated Learning method so that they can get the expected academic achievement. The application of successful Self-Regulated Learning and having a high levels of self-efficacy not only helps students in achieving academic achievement but also in dealing with problems in the world of work.